Synthesis of Zn-Fe nanoparticles using pulse laser ablation as a contrast agent in magnetic resonance imaging - Nurul Hikmantiyah; Eko Hidayanto; Ali Khumaeni (Diponegoro University Semarang Indonesia, 2019)
Synthesis of zinc oxide nanoparticles, iron oxide nanoparticles and Zn-Fe nanoparticles using pulse laser ablation method has been conducted. Experimentally, a pulse Nd:YAG laser (1064 nm, 7 ns, 35 mJ) was directed and focused on a metal plates of pure Zn and Fe, which are placed in the liquid medium of polyvinyl pyrrolidone (PVP). The PVP functions as a stabilizer agent. The results show that the produced nanoparticles have a spherical shape with an averaged diameter of Zn-Fe nanoparticles of 13 nm. FTIR and XRD test results of Zn-Fe nanoparticles show characteristics of Zn-Fe compounds. The examination of Zn-Fe nanoparticles as MRI contrast agents was carried out by varying the concentration of nanoparticles. Cenh calculation results showed the highest contrast enhancement occurred at a concentration of 1.25 mM with a value of 64.26% for T1 weighted images, and 81.52% for T2 weighted images. The SNR calculation results show the highest value at a concentration of 1.25 mM of 70.52 for T1 weighted images. The highest SNR value in the T2 weighted image at a concentration of 0.156 mM of 165.09.